2015
DOI: 10.1111/lam.12511
|View full text |Cite
|
Sign up to set email alerts
|

Recent strategies for efficient production of polyhydroxyalkanoates by micro-organisms

Abstract: Polyhydroxyalkanoates (PHAs) are polyesters accumulated by many bacteria under unbalanced growth conditions, and have been used to meet the various demands in areas of agriculture, medicine, and materials especially belong to a rapidly expanding area of biomedical research. Unfortunately, the high production cost than the traditional synthetic materials has greatly limited the wide application of PHA. Here, we systematically summarized recent progress in production of PHAs and a series of optimization strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 60 publications
(72 reference statements)
0
12
0
2
Order By: Relevance
“…In 2015, studies were mostly dedicated to reducing costs through the reuse of waste generated from PHA production or an increase in the generation of high added-value products (Wei et al, 2015). In addition, the identification of the weakest points in the process for implementation at industrial scale revealed the next research lines (Muhammadi et al, 2015;Chen et al, 2015a;Kaur and Roy, 2015;Liu et al, 2015). In 2016, authors had maintained attention on the improvement of genotypes and operational conditions of fermentation (Kawaguchi et al, 2016;Tai et al, 2016;Inoue et al, 2016).…”
Section: Scientific Impact Of Pha Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, studies were mostly dedicated to reducing costs through the reuse of waste generated from PHA production or an increase in the generation of high added-value products (Wei et al, 2015). In addition, the identification of the weakest points in the process for implementation at industrial scale revealed the next research lines (Muhammadi et al, 2015;Chen et al, 2015a;Kaur and Roy, 2015;Liu et al, 2015). In 2016, authors had maintained attention on the improvement of genotypes and operational conditions of fermentation (Kawaguchi et al, 2016;Tai et al, 2016;Inoue et al, 2016).…”
Section: Scientific Impact Of Pha Productionmentioning
confidence: 99%
“…Table 1 shows that most authors have focused on reducing the cost of the PHA production process. Different strategies have been used to reduce costs such as genetic studies Liu et al, 2015;Tai et al, 2016;Inoue et al, 2016); and optimization of the PHA purification/extraction step (Mohammadi et al, 2012;Liu et al, 2015;Kawaguchi et al, 2016); to obtain PHA compounds with higher economic value and/or promising new applications (Muhammadi et al, 2015;Anjum et al, 2016;6 2015; Mohan et al, 2016;Obruca et al, 2015); to re-use the bacterial biomass generated from PHA production (Wei et al, 2015); to reduce the energy consumption of the PHA production process (Mohammadi et al, 2012;Liu et al, 2015), integration into biorefinery systems (Jiang et al, 2016), and to improve the yield of PHA production (Liu et al, 2015;Kawaguchi et al, 2016).…”
Section: Scientific Impact Of Pha Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since about 45% of the total costs of PHA production are ascribed to carbon sources, such as refined glucose or sucrose. Therefore, cheap wastes or side products of agriculture and food industry, are used as inexpensive carbon substrates, improving thus the economic feasibility of the PHA production [2,3]. Further, the biotechnological production of PHAs is also complicated by the lack of fast and reliable analytical tools enabling the rapid and sensitive determination of PHAs in bacterial cells during the biotechnological process.…”
Section: Introductionmentioning
confidence: 99%
“…The production of PHA copolymers in recombinant bacteria able to combine HA SCL and HA MCL (P[3HB-co-3HA MCL ]) represents an interesting opportunity to develop new materials with intermediate properties and new applications [Tan et al, 2014;Anjum et al, 2016;Liu et al, 2016]. Given this, the development of stable chromosomal encoded genes in recombinant strains is desired in industrial bioprocesses and environmental applications to avoid the drawbacks of plasmid instability and the use of antibiotics [Lemuth et al, 2011;Nikel and de Lorenzo, 2013;Yin et al, 2014;Lee and Kim, 2015;Oesterle et al, 2017].…”
Section: Introductionmentioning
confidence: 99%